Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1002/humu.24057
|View full text |Cite
|
Sign up to set email alerts
|

Candidate genes for hereditary colorectal cancer: Mutational screening and systematic review

Abstract: Genome‐wide approaches applied for the identification of new hereditary colorectal cancer (CRC) genes, identified several potential causal genes, including RPS20, IL12RB1, LIMK2, POLE2, MRE11, POT1, FAN1, WIF1, HNRNPA0, SEMA4A, FOCAD, PTPN12, LRP6, POLQ, BLM, MCM9, and the epigenetic inactivation of PTPRJ. Here we attempted to validate the association between variants in these genes and nonpolyposis CRC by performing a mutational screening of the genes and PTPRJ promoter methylation analysis in 473 familial/ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 50 publications
1
47
0
Order By: Relevance
“…Very recently, we performed a mutational screening of RPS20 in 473 familial/early onset CRC cases and did not identify any predicted pathogenic variant. Taking the three studies together, we concluded that disruptive (stop-gain, frameshift, and start-loss) variants are enriched in familial/early onset CRC cases compared to controls [ 10 ]. Supporting this association with hereditary CRC, RPS20 c.177+1G>A has recently been identified in another family with four CRC-affected members, all of them carriers or obligate carriers of the RPS20 variant [ 11 ].…”
Section: Rps20 Mutations As a Rare Cause Of Hermentioning
confidence: 99%
See 4 more Smart Citations
“…Very recently, we performed a mutational screening of RPS20 in 473 familial/early onset CRC cases and did not identify any predicted pathogenic variant. Taking the three studies together, we concluded that disruptive (stop-gain, frameshift, and start-loss) variants are enriched in familial/early onset CRC cases compared to controls [ 10 ]. Supporting this association with hereditary CRC, RPS20 c.177+1G>A has recently been identified in another family with four CRC-affected members, all of them carriers or obligate carriers of the RPS20 variant [ 11 ].…”
Section: Rps20 Mutations As a Rare Cause Of Hermentioning
confidence: 99%
“…Aldubayan et al (2018) identified two additional carriers of MRE11 predicted pathogenic missense variants among 667 CRC patients [ 5 ], and Belhadj et al (2020) 2 more carriers in a 473-familial/early onset-CRC cohort. A meta-analysis of all reported series compared to a control population indicated that MRE11 -disruptive variants are significantly enriched in familial/early onset CRC, supporting the role of MRE11 in CRC predisposition [ 10 ]. On the other hand, it has been suggested that MRE11 and other MRN components may be used as biomarkers for predicting disease progression and treatment response.…”
Section: Candidate Causal Genes For Mismatch Repair Proficient Hermentioning
confidence: 99%
See 3 more Smart Citations